2011
DOI: 10.4103/0973-029x.80031
|View full text |Cite
|
Sign up to set email alerts
|

Microwave processing: A boon for oral pathologists

Abstract: Background:Research in oral and maxillofacial pathology has unlimited potential. We use every technology available to us for better and faster reliable diagnosis. But in most institutions, private laboratories and multispecialty hospitals, tissue processing takes considerable time, and therefore delays the diagnosis, which is required in urgent cases. We, in this institution, conducted a study to hasten the processing by using a simple kitchen microwave.Aim:To analyze tissue sections processed by microwave as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 13 publications
9
14
0
Order By: Relevance
“…This is consistent with other studies [12,23]. However, in our study the nuclear details were slightly less clear in microwave fixed tissues.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with other studies [12,23]. However, in our study the nuclear details were slightly less clear in microwave fixed tissues.…”
Section: Resultssupporting
confidence: 92%
“…This was similar to the findings of Hopwood D et al, [27] and Emerson LL et al, [32] who showed that malignant cells were equally well preserved by both conventional and microwave fixed tissues. Right from precancerous conditions and lesions to malignancy, reactive lesions to benign tumours, microwave technique has shown a remarkable difference without losing the architecture and morphology of the cells [23].…”
Section: Resultsmentioning
confidence: 99%
“…Though few authors had utilized chloroform for clearing [5], in the present study, the clearing was done with xylene, with satisfactory results. It was observed that a longer time was needed for the wax impregnation (30 minutes) as compared to that in the previous studies, where it ranged from five minutes to fifteen minutes [14].…”
Section: Discussionmentioning
confidence: 62%
“…The two methods did not show signiicant variation in terms of overall quality, consistent with the observations of numerous authors such as Rohr, Morales, Mathai, Devi, Babu. [1][2][3][4][5][6] Complete concordance of opinion with regard to quality of the two methods was seen in an average of 90.42% cases. Majority of tissue sections were of excellent quality (Score-4).…”
Section: Resultsmentioning
confidence: 81%
“…Total of 200 slides (100 pairs) were evaluated by each observer: O 1 and O 2 . Seven different parameters (1.Cellular clarity, 2.Cytoplasmic details, 3.Nuclear details, 4.Colour intensity, 5 .Interface of epithelium and connective tissue, 6.Fibrous tissue component and 7.Staining quality) were evaluated by two observers and independent scores were given as per obtained quality.…”
Section: Scoringmentioning
confidence: 99%